Analisis Manajemen Risiko Rantai Pasok Usahatani Cabai Rawit di Desa Bulontala Timur, Kabupaten Bone Bolango - Mohamad Alwis Saputra Gintue; Amelia Murtisari; Ramlan Mustafa (Agricultural Socio-Economic Empowerment and Agribusiness Journal, 2025)
Chili pepper is one of the vegetable plants that can be harvested repeatedly; not only that, but chili pepper also has high economic value and is rich in nutrients. This study aims to determine the level of risk occurrence of the chili supply chain in the Al-Hidayah farmer group, East Bulontala Village, and to determine the severity of the risk of the chili supply chain in the Al-Hidayah farmer group, East Bulontala Village. The method used is the Supply Chain Operation Reference (SCOR) to identify potential risks at each stage of the supply chain, from planning, production, to distribution. The results of the study showed that the level of risk occurrence at the farmer level was in the small risk category, with a total risk value reaching 141.2 and an average of 28.24. Furthermore, the level of risk at the trader level was in the small risk category with a total risk value of 127.7 and an average value of 25.54. Then, for the level of risk occurrence at the consumer level, it was in the small risk category with a total risk value of 163.2 and an average value of 32.64. Then for the level of risk severity at the farmer level is in the small risk category with a total value of risk severity of 199.6 and an average value of 39.92. Furthermore, the level of risk severity at the trader level is in the small risk category with a total value of risk severity of 169.7 and an average value of 33.94